The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.22146/jieb.9961
|View full text |Cite
|
Sign up to set email alerts
|

The Technology Readiness or Social Presence, Which One Could Explain the Technology Acceptance Better? An Investigation on Virtual Communities

Abstract: Internet technology has accelerated the development of communities from face-to-face into computer-mediated communications. Individuals who joined the virtual communities contributed greatly to building their knowledge by sharing their experiences. This study investigates the individuals' knowledge sharing intentions using two approaches for the research model. The first approach is adopted from Hung & Cheng's (2013)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…Raymond (2012) empirically showed that online social networking presence has positive influence on university students’ learning. Jubran and Sumiyana (2015) found that social presence and compatibility are integrated into the TAM, and could positively affect technology acceptance. Users who have strong social presence in virtual environment systems become immersed more easily.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Raymond (2012) empirically showed that online social networking presence has positive influence on university students’ learning. Jubran and Sumiyana (2015) found that social presence and compatibility are integrated into the TAM, and could positively affect technology acceptance. Users who have strong social presence in virtual environment systems become immersed more easily.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Existing studies on the relationship between TR and SP are scarce; they do, however, include a study on individuals' sharing of knowledge [40]. However, this study did not examine the direct relationship between TR and SP; instead, it examined how each dimension of TR and SP influenced the knowledge sharing intentions of its participants, based on the technology acceptance model (TAM) [41].…”
Section: Technology Readiness Social Presence Course Satisfaction And...mentioning
confidence: 99%
“…Hal ini sesuai dengan konsep teknologi readyness seperti yang dijelaskan oleh Blut & Wang (2020) dimana dimensi optimisme merepresentasikan pandangan positif terhadap teknologi dan persepsi terhadap manfaat teknologi dalam meningkatkan efisiensi pekerjaan dan meningkatkan kinerja seseorang di lingkungan kerja dan di rumah. Sedangkan Jubran & Sumiyana (2016) menjelaskan bahwa dimensi innovativeness mengacu pada tingkat dimana seseorang senang bereksperimen dengan teknologi dan menjadi yang terdepan dalam usaha mencoba produk atau jasa berbasis teknologi yang terbaru.…”
Section: Pentingnya Pengadaptasian Teknologi Dan Sistem Informasiunclassified